Transition Programming for Youth with Persistent Delinquent Histories: A Descriptive Case Example. Issue 3 (3rd July 2019) - McDaniel, Sara C.; Carter, Coddy
ABSTRACT: Detained youth experience noted struggles with reentry to school and the community and the first 6 months after release are critical for reentry to school or work for decreasing the rate of recidivism. For this community engagement research project, numerous partners including the University, local school district, local youth detention center, and family resource center were involved. This transition project provided transition support to three participants through: (a) electronic monitoring, (b) educational advocacy, (c) case management, and (d) in-school mentoring. The delinquent and social histories of each participant are described, as well as the descriptive findings from the wraparound intervention. Reentry, access to services, attendance, and recidivism data reflect intervention effectiveness.